Citizens' Options When Accessing and Sharing Health Information – An International Survey of IMIA Member Countries - Hjermitslev, Camilla; Monkman, Helen; Adler-Milstein, Julia; Schmidt, Thomas; Nøhr, Christian; Eriksen, Jeppe (Yearbook of Medical Informatics, 2024)
Introduction: Citizens' access to personal health information and information on prescription medication, options to share personal health data, and how these personal health data are kept secure, are all important themes in health informatics and therefore elaborated upon in this paper.Methods: The empirical data stems from a survey that examines citizens' temporal access to laboratory test results, options for sharing patient-generated health data (PGHD) with health providers, methods to obtain supplementary information on prescription medication, and security issues pertaining to national standards, education, and experienced breaches.Results: Results are based on answers from representatives in the International Medical Informatics Association (IMIA) member countries (n=28). Data shows that citizens' online access to test results is possible as soon as they are available in ten countries whereas nine countries have no norm or standard. The most common ways to provide citizens with supplementary information on prescription medication is through package inserts from manufacturers or paper medication information from pharmacies. PGHD is shared primarily in print or by showing the device to the health provider. Regarding e-health security, most countries have national standards for the security, however, less than half of the IMIA representatives answer that health professionals are required training in the national standards. Lastly, 16 of the 28 answers reply that there has been leaks leading to unauthorized access to health data. Future research should focus on how to provide citizens access to lab results according to their needs and examine how to include digital PGHD meaningfully into clinical practice.
Keywords: Consumer Health Informatics; Patient-generated Health Data; Accessibility; Personal Health Information; International Medical Informatics Association